The Effect Of Rehabilitation Exercises On Trunk Flexibility And Its Effect On Lower Back Pain In Physically Disabled Individuals - Hamdan, Husham; Mohammed, Ahmed; Abedulameer, Eman (Journal of Physical Education, 2017)
The problem of the research lies in many individuals with physical disability suffers from lower back pain. Clinical diagnosis of this pain showed that lower back pain is due to lack of flexibility. The aim of the research is to design rehabilitation exercises to improve trunk flexibility. The subjects were 17 physically disabled individuals with amputation aged 26 – 29 years old. Rehabilitation exercises were applied on the subjects for 6 weeks with 4 training sessions per week. The researchers concluded that there is an improvement in trunk flexibility that decreased low back pain for physically disabled individuals. The researcher recommended the necessity of using flexibility exercises to avoid lower back pain for the physically disabled